Neospora caninum: Imunoglobulinas como marcadores de infecção transplacentária e avaliação da susceptibilidade de cultivos celulares - Cadore, Gustavo Cauduro (2009)
Neosporosis is a parasitic disease of wide distribution and great importance to the cattle industry, mainly due to its associated reproductive losses. The life cycle of Neospora caninum typified by the tree know infectious stages: tachyzoites, tissue cysts with bradyzoites, and oocysts. Transmission routes can be horizontal and/or vertical. The vertical transmission or transplacentally is the most frequent form of infection, and an important form of maintain the agent in herds. With aim of to determine the occurrence of anti-Neospora caninum antibodies in serum samples of 260 bovine fetuses, collected in a slaughter in the municipality of Santa Maria, in Rio Grande do Sul, Brazil. For detection antibodies anti-N. caninum indirect fluorescent antibody test was used and immunoglobulin G and M were detected, using a cut-off 1:25. Of the 260 serum samples tested, 15% (39/260) were positive for the presence of anti-N. caninum. Of these, in 38 the presence of IgG where detected (97.4%) and in six IgM were present (10.3%). Five samples (15.4%) tested were positive for both IgG and IgM. The results reaffirming the ability of N. caninum in determine fetal infection. The results presented on the first chapter indicated that the search of IgM anti-N. caninum is of very limited help in the detection of the transplacental infection in cattle. In second chapter, was evaluated the susceptibility to infection by N. caninum in different cell cultures, for the purpose of observe the ability in vitro multiplication this agent. For this, eight cell cultures were tested, among the cell cultures tested, four presented good susceptibility to agent: cell lines VERO (yield of 21.2 tachyzoites/cell) and MA-104 (17.1); primary bovine testicle (16.3) and lung cells (13.6). Primary bovine kidney (8.2 tachyzoites/cell), MDBK (5.1) and RK-13 cell lines (0.4) presented moderate to low sensitivity. No viable tachyzoites were detected in the culture of MDCK cells. These results demonstrate that MA-104 cells present adequate susceptibility to N. caninum compared to VERO cells, which have been largely used to multiply the parasite in vitro. Due to the easy manipulation, quick multiplication and relatively low nutritional equirements, these results indicate that MA-104 cells are adequate for multiplication of N. caninum in vitro.